(untitled) (KONFERENSIYA, 2025)
India’s linguistic landscape, characterized by over 22 official languages and thousands of dialects, positions translation as a critical tool for cultural preservation, economic integration, and technological advancement. This paper explores modern trends in translation within the Indian context, focusing on the integration of artificial intelligence (AI), the resurgence of literary translation, audiovisual practices, and localization efforts. Drawing on recent scholarly works, government policies, and industry reports from 2023–2025, it examines how these trends address multilingualism while navigating challenges like data scarcity and cultural nuances. Key findings highlight the hybrid AI-human model as a dominant paradigm, the global recognition of Indian literary translations, and policy-driven initiatives for indigenous language support. The analysis underscores opportunities for equitable knowledge dissemination but warns of persistent barriers in low-resource languages. Recommendations include enhanced investment in AI training datasets and collaborative translation ecosystems to foster inclusivity